AN INTEGRATED MODEL OF FACTORS AFFECTING WEBSITE ADOPTION, PERCEIVED RISK AND TRUST ON ONLINE SHOPPING INTENTION IN CHINA - Xia, Zongwen; Chaipoopirutana, Sirion (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
With the growth of e-commerce platforms, more and more customers are changing their shopping intention from physical stores to online platforms. China has a substantial population in the world and also has the completed e-commerce platform. Due to Covid-19 Pandemic, many consumers changed their behavior to be online shopping. E-commerce still has a large potential market in near future. Therefore, this research aims to test the influence of website adoption, perceived risk, and trust on online shopping intention. The researchers collected the data from online shoppers who bought products service from one of the most famous online shopping websites in China. The sample of this study was collected from 400 respondents through online. Non-probability sampling methods including purposive and convenience sampling was applied to collect the data from the sampling units. The five-point Likert scale was designed for research instruments. Descriptive analysis and inferential analysis were applied to analyze the data and multiple linear regression analysis was applied to test all hypotheses. Based on the findings, the researchers found that perceived usefulness, perceived ease of use, social influence, and facilitating conditions significantly influenced online shopping intention. Perceived risk and trust also had a significant influence on online shopping intention.